The Effect of Post-Curing Sulphuric Acid Water Bath on Strong Concrete Press Comes from Three Different Sand Quarry - Yudhistira Saptapringga Riesky Sundani Sundani; Agyanatha Tua Munthe Tua Munthe (NAROTAMA UNIVERSITY, Indonesia, 2021)
Concrete is one of the construction materials that has been commonly used for building buildings, bridges, roads, and others. Concrete as well as other building structures, not separated from damage - damage that can reduce its durability, one of the reasons is because of external influences or the environment in which the concrete structure is located, such as in certain locations, for example in environments related to chemicals, sulfate, chloride, salt or those in marine areas. The purpose of the study was the effect of sulphuric acid water baths on confensional concrete and knowing the concrete with a mixture of sand from which areas were strong press higher after being soaked with sulphuric acid soaking. The research method used is to use the experimental method by mixing sulphuric acid compounds in water as a medium of concrete curing derived from three different sand quarys with variations in the composition of sulfuric acid compounds that are berberda umtuk get strong press results data from this study. From the results of this study, the conclusion that normal concrete derived from mountain sand namely Cimangkok sand (CMK), and Cigombong (BHM) is more resistant to sulphuric acid concentrations of 2% and 5%. Normal concrete derived from river sand i.e. Citarik sand (CTK) is not resistant to sulphuric acid concentrations of 2% and 5% which results in a lower press strength than mountain sand. Normal concrete derived from a mixture of river sand (Citarik) and mountain sand (Cimangkok and Cigombong) called Sand Mix (MX) is more resistant to sulphuric acid concentrations of 5% than other sand